Performance Comparison Modeling Between Single-phase Cycloconverters and Three-phase Cycloconverters Using Matlab Simulink Tools - Setiyono Setiyono; Bambang Dwinanto (Jurnal Ilmiah Teknik Elektro Komputer dan Informatika, 2021)
This paper presents a performance comparison of a single-phase AC to AC converter (cycloconverter) and a three-phase converter circuit which divides the input wave frequency (fin) into a variable frequency with the frequency value of the AC output voltage waveform (alternating current) (f, fin/2, fin/3, fin/4, fin/5, fin/6, fin/7, fin/8, fin/9, fin/10. Cycloconvertor switches are built using a diode and a thyristor device. This research was conducted by modeling each cycloconverter circuit using Matlab Simulink tools. Modeling simulation parameters to be analyzed include the output waveform RMS (root mean square) value, frequency value, and Total Harmonic Distortion (THD) index for each wave. The output frequency voltage waveform of cycloconverter is affected by the variation of the trigger signal of the P-side (positive) converter and the N (negative) converter side switch. Simulation results show that adjusting the firing pulse width of the P converter and the N converter will produce an output voltage wave that has an index value of THD, Vrms, and form factor for each diode and thyristor cycloconverter circuit.